Construção Arquitetônica Contemporânea: a obra de Gilberto Guedes - Rocha Júnior, Rui Vanderlei (2012)
This paper addresses the production of the architect Gilberto Guedes, from Paraiba. It outlines an overview of his architecture in order to, from the analysis of four projects of family housing, identify the contemporary assumptions of his work. The four chosen houses show a way of working with architecture that includes, in addition to his idiosyncrasies, specific aspects of the spirit of the period in which they were built, between 1990 and 2011. The strategies, mechanisms, procedures and formal artifacts recurring in his word are sought. Architect still actively working, Guedes has a production that was awarded and was also the subject of articles and publications of different calibers - local, national and international - and that shows his importance to the contemporary production. The architect is presented in the context of contemporary production, creating a profile that brings a particular perspective of architecture in Paraiba.